PENGARUH STRATEGI BISNIS DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN PADA USAHA KECIL MENENGAH SONGKOK ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œUDENG BALIÃƒÂ¢Ã¢â€šÂ¬Ã‚Â GENTENG BANYUWANGI - Ach Hasan Hasyim (NATUJA: Jurnal Ekonomi Syariah, 2022)
The tight competition in the business world, makes SMEs must have a business strategy and competitive advantage, both in knowledge and enterpeneurship ability, the creation of a sustained competitive advantage will create superior marketing performance acceptable to consumers. This study examines the influence of business strategy and competitive advantage on the marketing performance of MSMEs songkok "udeng Bali" in Genteng Banyuwangi district. With quantitative research methods, through an explanatory research approach, with the type of survey research research, the determination of sapel with Non Probability Sampling as for the most suitable is saturated sampling of 20 MSMEs, data analysis using t test (partial), F test (simultaneous) and R2 test using SPSS analysis tool. The results showed that the business strategy (X1) had a significant effect on the marketing performance of SME Songkok "Udeng Bali" Banyuwangi Tile, where the value (Standardized Coefficients) was positive at 0.480 with a Sig. of 0.009 ≤ 0.05. The competitive advantage (X2) is significant to the marketing performance of SME Songkok "Udeng Bali" Genteng Banyuwangi, where the value (Standardized Coefficients) is positive 0.480 with Sig. of 0.009 ≤ 0.05. Business strategy (X1) and competitive advantage (X2) have a significant effect on the marketing performance of SME Songkok "Udeng Bali" Banyuwangi Tile, with a calculated F value of ≥ F table of 17,879 ≥ 3.55 with Sig. By 0.000 ≤ 0.05.